Pengembangan Sumber Daya Manusia Pada Kecamatan Pesanggrahan Berbasis Otomasi Perkantoran Dengan Microsoft Excel - Arsanto Narendro (CV. Multi Kreasi Media, 2023)
Pesanggrahan sub-district, South Jakarta, is the South Jakarta administrative office which provides services to the Pesanggrahan community. In his duties, he provides many services to the community, including population data, processing family cards and birth certificates and other permits. The duties of sub-district employees are many and involve a lot of data. Of course it has its own level of difficulty. So to process this data, an application that is reliable in handling data is needed. Office automation-based software is software that is reliable in handling data, both in the form of documents and data processing using Microsoft Excel. The use of computer-based office automation also requires separate training so that sub-district officers become familiar with the software so that it can be put to good use in their field of work.